2021
DOI: 10.1016/j.jbusres.2021.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Prevision model and empirical test of box office results for sequels

Abstract: As studios release an increasing number of movie sequels, scholars have begun to examine this strategic choice. Prior studies use standard models of box office performance to evaluate sequels' performance and have mainly compared the box office results of the original movie with those of its sequel. However, sequels hold a unique position in the motion picture market since they are strongly associated with the original movie. Using the accessibilitydiagnosticity framework, this research investigates the driver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
(121 reference statements)
0
2
0
Order By: Relevance
“…When developing box office forecasts, it is critical to take sequels into account because sequels have a unique place in the motion picture business since they are connected with the original film. Studies have shown that reviews and ratings of the original film have a direct impact on the performance of the sequel [20], and many sequels have a marketing advantage with a reputation built up by the film's predecessor. Special Effect.…”
Section: Feature Descriptionmentioning
confidence: 99%
“…When developing box office forecasts, it is critical to take sequels into account because sequels have a unique place in the motion picture business since they are connected with the original film. Studies have shown that reviews and ratings of the original film have a direct impact on the performance of the sequel [20], and many sequels have a marketing advantage with a reputation built up by the film's predecessor. Special Effect.…”
Section: Feature Descriptionmentioning
confidence: 99%
“…Among them, the three major factors of celebrity influence, comment, and word of mouth have received extensive attention [9]. In addition, in view of the huge economic impact of film sequel products in the film industry, scholars have begun to study the impact of this factor [10]. With the explosive growth and development of digital technology, movie consumers can express their opinions or attitudes towards products across space and time.…”
Section: Introductionmentioning
confidence: 99%